Differences in motor skills of selected and nonselected group of children in artistic gymnastics in the context of their motor development - Šalaj, S.; Milcic, L.; Šimunovic, I. (Kinesiology, 2019)
Main purpose of this paper was to find differences in motor skill level between the selected and non-selected group of children in artistic gymnastics. Artistic gymnastics is one of the sports that is frequently put into a negative context because of early specialization of children, while at the same time it is considered to be basic, fundamental sport. Thirty-one children (age 5.59 ± 0.77 years) participated in this study. The data was collected using Test of Gross Motor Development - Second Edition (TGMD-2). One-way ANOVA and Bonferroni post-hoc test was used to determine the differences in motor skills of children. The results show differences in locomotor skills between the selected and the non-selected children gymnasts (p<.05). When comparing boys and girls, results show no gender differences in gross motor quotient, locomotor or manipulative skills. Although, there significant differences exist in gross motor quotient and locomotor skills in selected girls, compared to non-selected girls (p<.05). These results suggest that female competition program in preschool age favorizes development of locomotor but not manipulative motor skills. Regardless of the sport in which preschool children are enrolled, exercise should be multilateral. For this reason, in artistic gymnastic we should encourage multilateral development and inclusion of tests and exercises for manipulative skills which could have effect on child`s future overall (motor, social and psychological) development.